Ketidakberdayaan di Masa Pandemi Covid-19: A Literature Review - Kurniawan Kurniawan; Ai Indah Nazriah; Sri Rahayu; Rahmah Tresnala; Toni Arisandi; Khoirunnisa Khoirunnisa (FORIKES, 2021)
Background: Covid-19 is a pandemic that has an impact on psychological problems. Powerlessness is a psychological problem that causes individuals to be unable to carry out daily activities. Powerlessness arises as a result of bad perceptions in each individual. The purpose of the literature study is to describe the helplessness of everyone during the Covid-19 Pandemic. Our method uses the PICO search stage using relevant keywords for a period of 10 years (2011- 2021). There are 7 articles that are relevant as the main reference. The results of the literature study show that individuals feel helplessness as a result of the ongoing Covid-19 pandemic. Nurses can provide motivation or education as an intervention to overcome helplessness. Conclusion: Experience of helplessness during a pandemic can happen to everyone and a good coping mechanism is needed to deal with it.Keywords: Covid-19; helplessnessABSTRAKLatar belakang: Covid-19 merupakan masa pandemi yang memberikan dampak pada masalah psikologis. Ketidakberdayaan merupakan salah satu masalah psikologis yang menyebabkan individu tidak mampu melakukan aktivitas sehari-hari. Ketidakberdayaan muncul sebagai akibat dari persepsi yang tidak baik dalam setiap individu. Tujuan dari studi literatur adalah menggambarkan ketidakberdayaan setiap orang di masa Pandemi Covid-19. Metode studi ini menggunakan tahap pencarian PICO dengan menggunakan kata kunci yang relevan dalam jangka waktu 10 tahun (2011-2021). Terdapat 7 artikel yang relevan sebagai referensi utama. Hasil studi literatur menunjukan bahwa individu merasakan ketidakberdayaan sebagai akibat dari pandemi Covid-19 yang sedang berlangsung. Perawat dapat memberikan motivasi atau edukasi sebagai salah satu intervensi untuk mengatasi ketidakberdayaan. Kesimpulan: Pengalaman ketidakberdayaan saat pandemik dapat terjadi pada setiap orang dan perlu mekanisme koping yang baik untuk menghadapinya.Kata kunci: Covid-19; ketidakberdayaan